Ban the (plastic) bag? Explaining variation in the implementation of plastic bag bans in Rwanda, Kenya and Uganda - Behuria, Pritish (Environment and planning. C, Politics and space, 2021)
The environmental damage that plastic waste is causing has catalyzed government action against plastic bags around the world. Despite anti-plastic bag policies gaining traction globally, there has been limited investigation of why the implementation of bans has varied. The variation in implementing bans is particularly stark in East Africa, a region that has been at the forefront of plastic bag legislation. Rwanda’s implementation of a ban on plastic bags in 2008 has attracted widespread praise for its environmental leadership. Kenya adopted a plastic bag ban before Rwanda but implementation was consistently delayed until a stringent ban was finally imposed in 2018. In Uganda, despite bans being announced on four separate occasions, implementation continues to be delayed. This paper explains why some governments adopt and effectively enforce plastic bag bans while others reverse course or delay implementation. Existing literature has cited the comparative strength of plastic industries as the salient factor in explaining varied adoption of plastic bag bans. This paper argues that though the comparative business power of plastic industries explains whether bans are obstructed, it does not satisfactorily explain varied implementation. Instead, countries that pursue services-based development strategies, which prioritise externally dependent sectors like tourism, are more likely to implement plastic bag bans, which can help bolster their green credentials. For the Rwandan and Kenyan governments, presenting their countries as environmental leaders contributed to their goals of becoming a regional economic hub, reliant on services like tourism. The Kenyan government’s decision to eventually implement the ban was driven by a perceived need to compete with Rwanda for regional environmental leadership while supporting Kenya’s services-based economic development strategy. In contrast, Uganda’s comparatively larger discovery of oil and limited emphasis on services-based development explained the government’s lack of commitment to implementing a plastic bag ban.